In Pursuit of Distinctiveness: Transmembrane Nucleoporins and Their Disease Associations - Bindra, Divya; Mishra, Ram Kumar (Frontiers in Oncology, 2021)
The bi-directional nucleocytoplasmic shuttling of macromolecules like molecular signals, transcription factors, regulatory proteins, and RNAs occurs exclusively through Nuclear Pore Complex (NPC) residing in the nuclear membrane. This magnanimous complex is essentially a congregation of ~32 conserved proteins termed Nucleoporins (Nups) present in multiple copies and mostly arranged as subcomplexes to constitute a functional NPC. Nups participate in ancillary functions such as chromatin organization, transcription regulation, DNA damage repair, genome stabilization, and cell cycle control, apart from their central role as nucleocytoplasmic conduits. Thus, Nups exert a role in the maintenance of cellular homeostasis. In mammals, precisely three nucleoporins traverse the nuclear membrane, are called transmembrane Nups (TM-Nups), and are involved in multiple cellular functions. Owing to their vital roles in cellular processes and homeostasis, dysregulation of nucleoporin function is implicated in various diseases. The deregulated functioning of TM-Nups can thus act as an opportune window for the development of diseases. Indeed, mounting evidence exhibits a strong association of TM-Nups in cancer and numerous other physiological disorders. These findings have provided much-needed insights into the novel mechanisms of disease progression. While nucleoporin’s functions have often been summarized in the disease context, a focus on TM-Nups has always lacked. This review emphasizes the elucidation of distinct canonical and non-canonical functions of mammalian TM-Nups and the underlying mechanisms of their disease association.